Respuesta :
Let's simplify step-by-step.
8
x
3
−
x
−
(
10
x
−
5
x
2
−
3
x
3
)
Distribute the Negative Sign:
=
8
x
3
−
x
+
−
1
(
10
x
−
5
x
2
−
3
x
3
)
=
8
x
3
+
−
x
+
−
1
(
10
x
)
+
−
1
(
−
5
x
2
)
+
−
1
(
−
3
x
3
)
=
8
x
3
+
−
x
+
−
10
x
+
5
x
2
+
3
x
3
Combine Like Terms:
=
8
x
3
+
−
x
+
−
10
x
+
5
x
2
+
3
x
3
=
(
8
x
3
+
3
x
3
)
+
(
5
x
2
)
+
(
−
x
+
−
10
x
)
=
11
x
3
+
5
x
2
+
−
11
x
Answer:
=
11
x
3
+
5
x
2
−
11
x
Brainliest Please:)
Answer:
-11x-5x^2+5x^3
Step-by-step explanation;
8x^3-x-10x+5x^2+3x^3 (distribute the negative sign)
8x^3-3x^3 -x-10x (combine like terms)
5x^3-11x-5x^2
-11x-5x^2+5x^3 (put in Standard form)
Hope this helps tell me if you have any questions!